Transdizer o não dito: Maria Gabriela Llansol, a tradução intersemiótica e um possível para o ensino da literatura - Isadora Bellavinha Maciel (2019)
This work investigates critical and creative transcreation, intersemiotic translation and emerging notions of the work of Maria Gabriela Llansol, to launch the idea of interartistic and intermediatic translation practice as a possibility for literature teaching and for the development of agent-readers. For this, concepts of Haroldo de Campos, Walter Benjamin and Jaques Derrida around language and translation were articulated, as well as meanings of intersemiosis in Julio Plaza, and also some important notions of the llansonian work as Legent, Figure and bod´in´rite. We also analyze the interart work "Betwinto - a becaming house", created from the texts of the Portuguese writer, as a practical part of this research. Thus, in contrast to reading protocols established by school institutions, we risk the practice of teaching literature in the unpredictable didactics of multimodal transcreation.